接辞ミとサの複合形式ミサ・サミについて - 近藤, 研至; 228; コンドウ, ケンジ; 20215453; Kondo, Kenji (文教大学大学院言語文化研究科付属言語文化研究所, 2025)
This paper discusses the function of compound forms mi-sa and sa-mi formed by the suffixes mi and sa. There are many examples of X-sami, but not so many of X-misa. This is a result that reflects the functions of the nounifier sa and the noun phrase maker mi. In other words, the nounifier sa cannot be added to something that has been nounified with X-mi, but mi can be added to nouns due to its function after the “atarasii mikei.” Therefore, misa is inhibited, but sami is quite tolerated. From the above, it can be said that the word structure of X-sami is ［［X-sa］mi］, and the word structure of X-misa is ［［X-mi］sa］ departmental bulletin paper